Umetnostno besedilo in otrok (Otrok in knjiga, 1987)
The personality of the child develops also through the productive reception of literary works, as for instance: - when reading the child distinguishes the conotative elements of texts, so that he compares the author's aspects of reality with his own experiences of the world and builds his own model reality, - that he determines the meaning of the words through synonyms and antonyms, - that he finds the place in metaphorical condensations of the text, which are coherent and, - by influencing his sensibility with concealed information.
Keywords: jezikoslovje; slovensko